miR394 Acts as a Negative Regulator of Arabidopsis Resistance to B. cinerea Infection by Targeting LCR - Tian, Xing; Song, Liping; Wang, Yi; Jin, Weibo; Tong, Fudan; Wu, Fangli (Frontiers in Plant Science, 2018)
Gray mold of tomato is caused by the pathogen Botrytis cinerea. MicroRNAs play a crucial role in the biotic and abiotic stress responses of plants and regulate their targets by gene silencing. MiR394 is an ancient and conserved miRNA in plants, and it participates in the regulation of plant development and stress responses. In our previous study, miR394 was found to respond to B. cinerea infection in tomato, but the roles and regulatory mechanisms of miR394 in B. cinerea-infected tomato remain unclear. MiR394 was down-regulated in tomato in response to B. cinerea infection, showing an expression pattern opposite to the previous finding that miR394 was up-regulated in tomato cv. Jinpeng 1 infected by B. cinerea. We obtained transgenic Arabidopsis overexpressing miR394, which resulted in low expression levels of its target LEAF CURLING RESPONSIVENESS (LCR). Leaf lesion size and trypan blue staining showed that miR394 overexpression led to increased sensitivity of transgenic Arabidopsis to B. cinerea compared to wild type. We also detected changes in the expression levels of stress-related miRNAs, including miR159, miR156, miR168 and miR172. In the transgenic plants, it indicated potential cross talk between these miRNAs and miR394, except for miR159. MiR394 also enhanced the expression of ARGONAUTE 1 (AGO1), DSRNA-BINDING PROTEIN 4 (DRB4) and the RNA-binding protein gene DAWDLE (DDL), which are involved in the pathways of miRNA biosynthesis and regulation, suggesting that miR394 overexpression has a feedback effect on these genes. Our data indicate that overexpression of miR394 in Arabidopsis increased the susceptibility of plants to B. cinerea by affecting the expression of its target gene LCR along with a number of key genes involved in plant miRNA metabolism (AGO1). Thus, miR394 is a negative regulator of Arabidopsis resistance to B. cinerea infection by targeting LCR.